Transformational Leadership and Incivility: A Multilevel and Longitudinal Test - Bureau, J.; Gagné, Marylène; Morin, A.; Mageau, G. (Sage Publications, 2017)
This research examines group-level perceptions of transformational leadership (TFL) as negative longitudinal predictors of witnessing person-related (e.g., insults/affronts) and work-related (e.g., negation/intentional work overload) acts of incivility at work. Witnessing workplace incivility was also postulated to negatively predict employee need satisfaction. Data were collected among production employees in different Canadian plants of a major manufacturing company (N = 344) who worked for 42 different managers (Mgroup size= 9.76). Two waves of data collection occurred 1 year apart. Results from multilevel analyses showed that workgroups where managers were perceived to engage in more frequent TFL behaviors reported reduced levels of person- and work-related incivility 1 year later. However, group-level incivility did not predict change in group-level need satisfaction 1 year later. At the individual level, results showed that witnessing higher levels of person-related incivility than one’s colleagues predicted reduced satisfaction of the need for relatedness 1 year later. These longitudinal findings build upon previous literature by identifying TFL as a potential managerial strategy to reduce incivility in workgroups over time. They also show that mere exposure to workplace misbehavior still affects employees’ adjustment, suggesting that every effort to reduce deviance in workplaces is worthwhile.